Analisis Biaya pada Perguruan Tinggi Politeknik Sebagai Dasar Penentuan Biaya Per Mahasiswa (Unit Cost): Studi Kasus Politeknik Caltex Riau - Tobi Arfan; Ria Nelly Sari; Zulbahridar Zulbahridar (Politeknik Caltex Riau, 2015)
Politeknik Caltex Riau (PCR) is one of the private educational institutions, where income from student tuition fees is the main income to run its operations. Therefore, it is very important for PCR to conduct an analysis of the cost per student per semester. It can be used as a basis for determining the fees to be paid by each student every semester and can maintain the competitiveness of each department with other private educational institutions. The aims of this study are to determine how much the unit cost per student and how much student from engineering and social department has to pay. PCR Cost analysis is performed by using the Time-Driven Activity Based Costing (TDABC) approach to allocate the cost from supporting departments to the main departments and then allocate costs to cost objects such as students. The results show that tuition fee per student of engineering departments is higher than the social department. There are five engineering departments: Electronics, Computer, Mechatronics, Telecommunications and Information Systems where the student tuition fee is smaller than the unit cost given. Thus, in order to cover the unit cost and maintain the quality and competitiveness, PCR should recalculated the unit cost per student to set reasonable tuition fee.Key words: Unit costs, tuition fees, competitiveness, Time Driven Activity Based Costing (TDABC)..